The management of syndesmotic screw in ankle fractures - Pogliacomi, Francesco; Artoni, Carlotta; Riccoboni, Sara; Calderazzi, Filippo; Vaienti, Enrico; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2018)
Background and aim: There is a wide debate about the number, diameter and length of the syndesmotic screw and necessity and timing for its removal. The aim of this study is to determine whether functional and radiological outcomes differ in patients operated for Weber type B and C ankle fractures who had syndesmotic screws removed (group 1) compared to those who did not (group 2). Furthermore, authors want to define if it is really necessary to remove this device and its correct timing. Materials and Methods: 90 patients were eligible for the study. The functional outcomes were analyzed 1 year after surgery using OMAS and AOFAS scores. Radiographic evaluation assessed the tibiofibular distance immediately and 12 months after surgery and fracture’s healing. Results: Clinical and x-rays results were similar in both groups at follow-up. Discussion: Fractures with interruption of syndesmosis are lesions that, if not well treated, are complicated by joint stiffness, residual pain and post-traumatic osteoarthritis. Syndesmotic screw removal is not routinely performed, thus accepting the risk of rupture but avoiding a new surgery. Conclusions: Results observed suggest that syndesmotic screw removal is not necessary. If surgeon decide to remove this device correct timing is mandatory in order to obtain satisfactory long-term results.